Introducing stereotactic radiotherapy safely: credentialing centres and staff. (June 2019) - Perkins, A; Aland, T; Dally, M; Jhala, E; Bailey, N; Shannon, D; Anderson, L
Abstract: Stereotactic radiotherapy treatments use high doses of radiation delivered in relatively few fractions compared with conventional radiotherapy. Specialist planning, immobilization and image guidance techniques are needed to achieve accurate treatment. Because doses are high and fractions few, the consequences of treatment errors are more severe than for conventional therapy. A credentialing program for staff and equipment is one strategy that can be used to reduce risk. The Icon Group runs a network of 20 radiotherapy centres in Australia. There has been a rapid growth of stereotactic treatments at Icon. In order to reduce the risks of introducing stereotactic therapy, an in-house credentialing and endorsement program was developed. A multi-disciplinary working group comprising medical physicists, radiation oncologists and radiation therapists was established to develop endorsement policies and procedures. Elements considered included the purchase, commissioning and quality assurance of equipment, the establishment and documentation of safe work practices and staff competency assessment. The endorsement program is in the process of being implemented across the Icon network.